American exceptionalism in the age of globalization : the specter of Vietnam - Spanos, William V. (State University of New York Press, 2008)
"In American Exceptionalism in the Age of Globalization, William V. Spanos explores three writers - Graham Greene, Philip Caputo, and Tim O'Brien - whose work devastatingly critiques the U.S. intervention in Vietnam and exposes the brutality of the Vietnam War. Utilizing poststructuralist theory, particularly that of Heidegger, Althusser, Foucault, and Said, Spanos argues that the Vietnam War disclosed the dark underside of the American exceptionalist ethos and, in so doing, speaks directly to America's war on terror in the aftermath of 9/11"--Jacket